Lipid-based nutrient supplements for pregnant women reduce newborn stunting in a cluster-randomized controlled effectiveness trial in Bangladesh. Issue 1 (25th November 2015) - Mridha, Malay K; Matias, Susana L; Chaparro, Camila M; Paul, Rina R; Hussain, Sohrab; Vosti, Stephen A; Harding, Kassandra L; Cummins, Joseph R; Day, Louise T; Saha, Stacy L; Peerson, Janet M; Dewey, Kathryn G
ABSTRACT: Background: Maternal undernutrition and newborn stunting [birth length-for-age z score (LAZ) <−2] are common in Bangladesh. Objective: The objective was to evaluate the effect of lipid-based nutrient supplements for pregnant and lactating women (LNS-PLs) on birth outcomes. Design: We conducted a cluster-randomized effectiveness trial (the Rang-Din Nutrition Study) within a community health program in rural Bangladesh. We enrolled 4011 pregnant women at ≤20 gestational weeks; 48 clusters received iron and folic acid (IFA; 60 mg Fe + 400 μg folic acid) and 16 clusters received LNS-PLs (20 g/d, 118 kcal) containing essential fatty acids and 22 vitamins and minerals. Both of the supplements were intended for daily consumption until delivery. Primary outcomes were birth weight and length. Results: Infants in the LNS-PL group had higher birth weights (2629 ± 408 compared with 2588 ± 413 g; P = 0.007), weight-for-age z scores (−1.48 ± 1.01 compared with −1.59 ± 1.02; P = 0.006), head-circumference-for-age z scores (HCZs; −1.26 ± 1.08 compared with −1.34 ± 1.12; P = 0.028), and body mass index z scores (−1.57 ± 1.05 compared with −1.66 ± 1.03; P = 0.005) than those in the IFA group; in adjusted models, the differences in length (47.6 ± 0.07 compared with 47.4 ± 0.04 cm; P = 0.043) and LAZ (−1.15 ± 0.04 compared with −1.24 ± 0.02; P = 0.035) were also significant. LNS-PLs reduced the risk of newborn stunting (18.7% compared with 22.6%; RR: 0.83; 95% CI: 0.71, 0.97) and small head size (HCZ <−2) (20.7% compared with 24.9%; RR: 0.85; 95% CI: 0.73, 0.98). The effects of LNS-PL on newborn stunting were greatest in infants born before a 10-wk interruption in LNS-PL distribution ( n = 1301; 15.7% compared with 23.6%; adjusted RR: 0.69; 95% CI: 0.53, 0.89) and in infants born to women ≤24 y of age or with household food insecurity. Conclusion: Prenatal lipid-based nutrient supplements can improve birth outcomes in Bangladeshi women, especially those at higher risk of fetal growth restriction. This trial was registered at clinicaltrials.gov as NCT01715038.